Physique as a risk factor for ulnar variance in elite female gymnasts - Claessens, A. L.; Lefevre, J.; Beunen, G.; de Smet, L.; Veer, A. M. (Medicine & Science in Sports & Exercise, 1996)
The aims of this study were: 1) to determine ulnar variance variability of elite, female gymnasts; 2) to evaluate the relationship between ulnar variance and physique, maturity status, and training characteristics of these gymnasts. All 156 skeletally immature female gymnasts were participants at the World Championships Artistic Gymnastics, Rotterdam, The Netherlands, in 1987. Chronological ages varied between 13.1 and 20.6 yr (mean = 15.9 +/- 1.3 yr). A large set of anthropometric dimensions was taken and somatotype was determined by the Heath-Carter technique. Skeletal age was assessed by the Tanner-Whitehouse II method. Menarcheal status and training data were collected by questionnaire. Ulnar variance was determined according to Hafner et al. Gymnasts differ significantly from reference girls with respect to physique and maturational status: gymnasts were smaller and delayed in skeletal maturity with about 1.5 yr. For those who had attained menarche, mean age at menarche was 15.1 +/- 1.3 yr. Ulnar variance shows a normal distribution in the gymnasts, ranging from -10.5 mm to +5.9 mm, which is somewhat more positive, i.e., an ulnar overgrowth, than reference wrists. The relationship between ulnar variance and somatic and maturational features suggests that female gymnasts who are more mature and have a physique characterized as relatively tall with a high lean body mass are at greater risk for developing a positive ulnar variance. No relationship between ulnar variance and training characteristics was evident. It is concluded that the observed positive ulnar variance in this sample of elite female gymnasts is less pronounced than originally stated in most "case reports."